PSYCHOLOGICAL FEATURES OF THE MANIFESTATION OF THE EVALUATION COMPONENT OF MOTIVATION IN SENIOR PRESCHOOL CHILDREN WITH COGNITIVE DISORDERS OF DEVELOPMENT - Buzhynetska, Kseniia (Psihologìčnij časopis (Online), 2023)
The article analyzes psychological and pedagogical sources on the peculiarities of the evaluation component of motivation. It has been outlined that, in general, motivation is considered as external, which arises in the process of achieving the goals of those educational tasks that are not related to the cognitive interests of the subject (motivation to avoid failure) and internal, which arises as a result of the subject's desire for self-development, self-improvement. It has been determined that the peculiarities of the motivation of children with cognitive disorders include those that have a certain peculiarity of purposefulness, which is manifested in the incorrect orientation in the task, erroneous and partial performance, inadequate attitude to the difficulties that arise, uncritical attitude to the evaluation of the result of educational and cognitive motives. It has been determined the main ways of formation of the evaluative component of motivation, which are interpreted as a personal formation that directly affects the regulation of behavior and activity, as an autonomous characteristic of the individual, its central component, which is formed with the active participation of the individual and reflects the originality of his or her inner world. The relevance of this problem is due to the fact that the senior preschool age is an important period for the formation of the evaluation component of the preschooler's motivation, its further development and influence on the personality. It has been revealed the leading role of the evaluative component of motivation, which is decisive for the successful learning and adaptation of the child to school in the future, since in the future the child must learn to find the mistakes made by comparing the results of his/her work with the sample; independently evaluate the results of his/her activity according to the guidelines given by the teacher (correct or not, what exactly; what is the identified error; what needs to be changed, what needs to be avoided in the next one and the ability to express self-evaluative judgments). It has been identified the criteria of the assessment component of motivation in senior preschoolers with cognitive developmental disorders. They are: consistency / inconsistency between the educational motive and the child's needs; the ability to subordinate intermediate goals to the overall goal; the ability to control their own activities, i.e. to exercise self-control; the ability to independently evaluate their own activities. It has been determined ways of correcting the evaluative component of motivation in older preschoolers with cognitive developmental disorders, which are aimed at its formation.